Desempenho agronômico, qualidade fisiológica e atividade enzimática de sementes de soja sob diferentes doses de glifosato - Castro, Douglas Goulart (2016)
The Roundup Ready technology has emerged to improve the planning of operations within the rural property, facilitating the control of weeds in post-emergence of the crop through the use of the herbicide gifosato. However, field observations, carried out in recent years have indicated that too much use of glifosato has caused injuries in the productive and physiological performance of plants. Therefore, two experiments was conducted, one evaluating the influence of glifosato doses of the components of production and agronomic traits in transgenic soybean crops and the other the effect that the herbicide promotes seed quality and enzyme analyses. In the first work, the experiment was conducted in two locations, one at the Centro de Desenvolvimento Científico e Tecnológico em Agropecuária da Universidade Federal de Lavras, Federal University of Lavras, in Lavras - MG and the other at the Fazenda Experimental da Empresa de Pesquisa Agropecuária de Minas Gerais, EPAMIG, in the city of Patos de Minas, MG, during the 2014/15 crop. 18 treatments were used with three replications, composed of three cultivars and six glifosato doses, in an RBD in a 3 x 6 factorial. The plot consisted of two 5 m rows, with 0.5 m between rows. Data were sumitted to joint variance analysis. It can be concluded that there is no effect of increased glifosato levels in soybean cultivars on production of components and agronomic traits. The use of high doses of glifosato in plants provides phytotoxic effects only during the first days after application. Cultivars showed different answers ahead of glifosato doses, for the percentage of phytotoxicity assessments. In the second study, the experiment was conducted at the Laboratório Central de Análises de Sementes of UFLA, with soybean samples from the two sites already mentioned. The experiment was conducted by adopting a completely randomized design in a factorial 3 x 6, with three cultivars and six doses of glifosato, adopting two replications. Germination Tests were performed, Water Content, Controlled Emergency, Accelerated Aging, Electrical Conductivity, Tetrazolium Test and Enzyme Analysis were conducted. It was concluded that there was a definite and specific response of increasing doses of glifosato in the final quality of transgenic soybean seeds. Cultivars showed different responses as to the physiological quality of seeds for the treatments. The greater or lesser expression of enzymes are associated with physiological quality of different genotypes of soybean seeds with environmental characters.